IMPLEMENTASI ENTERPRISE RESOURCES PLANNING (ERP) PADA BISNIS WARALABA Kentucky Fried Chicken (KFC) - A A Gde Satia Utama; Windi Apriliani; Silvia Candra Prastika; Ayu Pramita Sukarno Putri; Shela Ardika (Faculty of Economics and Business, Universitas Warmadewa, 2019)
KFC is the largest and most famous chicken restaurant in the world with restaurant chains in more than 10,000 locations spread across 80 countries. KFC has more than 2000 franchises spread throughout the world. the large number of franchises owned by KFC has caused report integration to be difficult to validate and management has difficulty tracking inventory stocks. With this, KFC is burdened by several sources that are not integrated, resulting in a lot of time and money lost for the duplication of order entries and business processes in all outlets. The reason behind this problem is evident from systems that cannot communicate with each other. Therefore KFC Franchising updates the structure of corporate information technology supported by the use of computerized information systems that are closely related to the operation support system (OSS) and managing support system (MSS) as a solution to the problems that have been faced. Where this information system is used to maintain quality control programs for restaurant services so that the company's operations continue to run sustainably for the creation of product excellence and to develop and apply new ideas by making financial statements a measure to measure their contribution to business. Keyword: Benefit and Risk; Enterprise Resource Planning (ERP); frenchise; implementation; managing support system (MSS); operation support system (OSS)